Flow enhancement in liquid composite molding processes by online microwave resin preheating. Issue 10 (8th July 2020) - Rubino, Felice; Esperto, Vitantonio; Tucci, Fausto; Carlone, Pierpaolo
Abstract: Liquid composite molding techniques are increasingly applied for the manufacturing of fiber‐reinforced plastic components for civil, aerospace, and automotive applications. Being the preform impregnation a key step during the process, resin viscosity should meet the precise requirements. Opportune resin preheating increases its fluency, thus enhancing the impregnation and saturation flow through the fabric and reducing the mold filling time. This paper explores the application of microwave technology for resin preheating. The integration of an online microwave preheating system within a demonstrative resin infusion facility is described and the effects of preheating on the infusion time are discussed. Parallel‐plate dielectric sensors were embedded into the mold to track the unheated and preheated resin flow through the fiber preform. The obtained results highlighted the effectiveness of online microwave heating to reduce the time required for the impregnation of the dry fiber reinforcement. Abstract : Microwave preheating system integrated online with resin infusion process allows to reduce the resin viscosity and enhance the flow through the fibrous reinforcement. Significant reduction of filling time can be achieved by increasing the resin temperature in the optimal range.